COMPARATIVE STUDY OF THE ECONOMIC DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN PAKISTAN, INDIA AND INDONESIA - Azam, Muhammad (Journal of Indonesian Economy and Business, 2011)
In this study an attempt has been made to investigate the effects of economic factors onÂ foreign direct investment (FDI) inflows into Pakistan, India and Indonesia. Simple loglinear regression model for each country has been used and the method of least squaresÂ has been applied. Empirical results show that market size, domestic investment, tradeopenness, and physical infrastructure are the important economic determinants of FDI.Further, this study also found that the empirical results of the economic determinants ofÂ India matched with empirical results of Pakistan except two determinates (i.e., tradeopenness and government consumption), while that of Indonesia do not match withÂ Pakistan and India. For attracting more FDI into Pakistan and India, the managementÂ authoritiesâ needs to ensure economic and political stability, provision of infrastructure,Â peace and security, encouraging domestic investment and adoption of appropriateÂ macroeconomic stabilization policy. Furthermore, this study recommend the sameÂ measures for Indonesia and suggest that more future research work are required forÂ empirical investigation of determinants of FDI in Indonesia, to enhance the desirable levelÂ of FDI into the country.Keywords: foreign direct investment, Pakistan, India, Indonesia